Development of Smart Parking Systems using RFID Sensors for Online Verification in Different Areas - Dhetryansah, Andi; Suhartono, Suhartono; Lamada, Mustari S; Zain, Satria Gunawan; Sanatang, Sanatang (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
This research aims to develop an intelligent parking system with online authentication in different areas using RFID sensors and to confirm the development results of the system through functional tests. This research is research and development (R&D) using a prototype model. The data were then analyzed using qualitative descriptive analysis techniques. The result of this study is an intelligent parking system that uses RFID sensors for online authentication in different areas, and the test results show that the average card authentication time at parking portals in different areas is 2.3 seconds. Based on the test results, the resulting smart parking system using RFID sensors for online verification in different areas can work as expected.